Additive value of 99mTechnetium methylene diphosphonate hybrid single-photon emission computed tomography/computed tomography in the diagnosis of skull base osteomyelitis in otitis externa patients compared to planar bone scintigraphy - Jehan Younis (World Journal of Nuclear Medicine)
The aim of this study was to evaluate the additive value of 99mtechnetium methylene diphosphonate (99mTc-MDP) hybrid single-photon emission computed tomography/computed tomography (SPECT-CT) in the diagnosis of skull base osteomyelitis (SBO) compared to planar bone scintigraphy (PBS). This was a single institution; prospective study included 23 patients with otitis externa, clinically suspected of SBO, all of them were diabetic. Three-phase bone scintigraphy and SPECT/CT were performed to all patients. The imaging modalities which had the most equivocal results were PBS (9/23) followed by SPECT (3/23). No equivocal results were detected with CT or SPECT-CT. SPECT-CT had the highest sensitivity (100%) and highest accuracy (95.7%) in diagnosis of SBO, whereas, PBS showed the lowest sensitivity (50%) and lowest accuracy (52.2%). In this study, SPECT-CT considered the best modality for accurate localization of the site of SBO involvement, followed by CT. SPECT and planar BS were less accurate in this consideration. When comparing the sensitivity of planar BS, CT, SPECT and SPECT/CT, statistical significance difference was detected between planar BS and SPECT (P = 0.057), planar BS and SPECT/CT (P = 0.001), and between CT and SPECT/CT (P = 0.031). No statistically significant difference was detected between SPECT and SPECT/CT (P = 0.250), CT and planar BS (P = 0.125), and between CT and SPECT (P = 0.508) In conclusion, 99Tc-MDP SPECT/CT has high sensitivity in the diagnosis of SBO and also provide accurate localization of the site of SBO.